Evaluación del riesgo ergonómico en el proceso de conteo de dinero y su incidencia en la aparición de enfermedades osteo musculares de miembros superiores en el personal del área de cajas con mayor transaccionalidad de una empresa financiera en la ciudad de quito. Propuesta de la introducción de máquinas recontadoras de dinero. - Carpio Cabrera, David Sebastián (2017)
Ergonomics is paramount in safety and health issues, the authorities in Ecuador have reformed the regulations with the aim of preserving the safety and health of employees of companies. The present Project was based on the ergonomic analysis of the Cashier Workstation of the parent agency of a financial institution in order to determine whether work activities have a direct incidence on the appearance of osteomuscuales diseases in the upper limbs. For the ergonomic analysis it was applied JSI method (Job Strain Index), according to the results thrown out by JSI method it was observed that 60% of the company´s population presents an INSURANCE risk level for money counting activity for the upper right limb as in the left, 20% presents a risk considered IMPROVEMENT and the remaining 20% presents a risk considered DANGEROUS, it was concluded that the combination of the technical actions speed and the posture of the wrists when executing the activities that involve repetitive movements can generate a high risk on the incidence of musculoskeletal conditions of the upper limbs. Was considered as a viable solution to reduce the ergonomic risk level for repetitive movements, the introduction of Money counting machines in cashier laboral activities, this way the manual money count be eliminated and rest times would extend decreasing exposure to ergonomic risk.